1997
DOI: 10.1007/s001120050137
|View full text |Cite
|
Sign up to set email alerts
|

Townes-Brocks-Syndrom

Abstract: BeimTownes-Brocks-Syndrom (TBS) handelt es sich um eine familiä r auftretende Fehlbildungskombination von Daumen-, Ohr-und Analanomalien in unterschiedlicher Ausprä gung. Erstmals beschrieben 1972 die Pä diater Townes und Brocks dieses Dysmorphiesyndrom bei einem Vater und 5 seiner 7 Kinder [24]. Im folgenden soll eine Familie mit 3 an TBS erkrankten Mitgliedern vorgestellt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Townes-Brocks syndrome (TBS; MIM 107480) was first described by Townes and Brocks (1972) as an association of imperforate anus, supernumerary thumbs, malformed ears, preauricular tags, and sensorineural hearing loss. Since the first description, several additional families have been described and several isolated cases have been reported (Reid and Turner 1976;Kurnit et al 1978;Walpole and Hockey 1982;Barakat et al 1988;de Vries-van der Weerd et al 1988;O'Callaghan and Young 1990;Rossmiller and Pasic 1994;Wischermann and Holschneider 1997). However, the frequency of this condition has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Townes-Brocks syndrome (TBS; MIM 107480) was first described by Townes and Brocks (1972) as an association of imperforate anus, supernumerary thumbs, malformed ears, preauricular tags, and sensorineural hearing loss. Since the first description, several additional families have been described and several isolated cases have been reported (Reid and Turner 1976;Kurnit et al 1978;Walpole and Hockey 1982;Barakat et al 1988;de Vries-van der Weerd et al 1988;O'Callaghan and Young 1990;Rossmiller and Pasic 1994;Wischermann and Holschneider 1997). However, the frequency of this condition has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation of TBS is highly variable (de Pina-Neto 1984;O'Callaghan and Young 1995;Wischermann and Holschneider 1997) both within and between affected families. Characteristic features of TBS are anorectal abnormalities (imperforate anus), abnormalities of the hands (preaxial polydactyly, triphalangeal thumbs), abnormalities of the feet (syndactyly, club foot), deformities of the outer ear ("lop ears") and preauricular tags, and sensorineural hearing loss (Rossmiller and Pasic 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first primer set consisted of a forward primer designed on the cDNA sequence 5' of the site of insertion (DHCR 930-949 ) and a reverse primer designed on the 134 bp insertion sequence (DHCR-ins 113-95 ), which amplified a genomic DNA fragment of approximately 2 kb. The second set consisted of a forward primer designed on the 134 bp insertion sequence (DHCR-ins [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] ) and a reverse primer designed on the cDNA sequence 3' of the site of insertion (DHCR 996-978 ), which amplified a genomic DNA fragment of approximately 120 bp. Taken together, these results indicated that the 134 bp insertion resulted from a partial retention of the 3' end of an intron with an approximate size of 2 kb.…”
mentioning
confidence: 99%
“…This amplification produced two overlapping fragments of 1073 and 650 bp, respectively (fig 3). The cDNA containing the 134 bp insertion was specifically amplified using the same 5' and 3' region primers in combination with the DHCRins 113-95 and DHCR-ins [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] primers designed on the insertion DNA sequence. This amplification produced two overlapping fragments of 1170 and 748 bp, respectively ( fig 3).…”
mentioning
confidence: 99%